Answer:
2. Substitution property
3. Given
4. Definition of congruent angles
5. Substitution property
6. Subtraction property of equality
7. Definition of congruent angles
8. Given
9. Definition of equilateral triangle
11. SAS (10, 7, 9)
Step-by-step explanation:
Answer:
= - 21
+ 6x² + 1
Step-by-step explanation:
Differentiate each term using the power rule
(a
) = na![x^{n-1}](https://tex.z-dn.net/?f=x%5E%7Bn-1%7D)
Given
y = - 3
+ 2x³ + x , then
= (7 × - 3 )
+ (3 × 2)x² + (1 × 1 )![x^{0}](https://tex.z-dn.net/?f=x%5E%7B0%7D)
= - 21
+ 6x² + 1
Answer:
308?
Step-by-step explanation:
Answer:
D
All the other ones were correct sooo